Impact of functional focal versus diffuse coronary artery disease on bypass graft patency. (1st November 2016) - Shiono, Yasutsugu; Kubo, Takashi; Honda, Kentaro; Katayama, Yosuke; Aoki, Hiroshi; Satogami, Keisuke; Kashiyama, Kuninobu; Taruya, Akira; Nishiguchi, Tsuyoshi; Kuroi, Akio; Orii, Makoto; Kameyama, Takeyoshi; et al.
Abstract: Background: Pressure guidewire pullback recording can differentiate between functional focal and diffuse disease types in coronary artery disease. The aim of this study was to compare the outcome of coronary artery bypass graft (CABG) patency between patients with functional focal versus diffuse disease types in recipient coronary arteries. Methods and results: We investigated 89 patients who underwent pressure guidewire pullback in the left anterior descending (LAD) artery before CABG using internal mammary artery (IMA). Based on the pressure guidewire pullback data, the LAD lesions were classified into functional focal disease (abrupt pressure step-up; n = 58) or functional diffuse disease (gradual pressure increase; n = 31). Follow-up computed tomography (CT) angiography was conducted within 1 year after CABG to assess the bypass graft patency. Pre CABG, LAD angiographic percent diameter stenosis (57 ± 10% vs. 54 ± 12%, p = 0.228) and fractional flow reserve (FFR) (0.68 ± 0.07 vs. 0.69 ± 0.07, p = 0.244) were not different between the functional focal and diffuse disease groups. The CABG procedure characteristics were similarly comparable between the two groups. In the follow-up CT angiography after CABG, occlusion or string sign of the IMA graft to LAD was more frequently observed in the functional diffuse disease group than in the functional focal disease group (26% vs. 7%, p = 0.021). Conclusion: In CABG, functional diffuse disease in the recipient coronary artery was associated with an increased risk of the graft failure in comparison with functional focal disease.